Innovations in Regulation of Simplified Procedure in Serbian Code of Criminal Procedure from 2011 - Brkić, Snežana S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Abstract: In this paper the author presents the evolution of the simplified procedure in Serbia from 2001 to 2011. He points to some legal innovations in this field during that deccenium. He compares old and new legal provisions about simplified procedure and finds some differences. There is a constant tendency to expanding the area of criminal offences which can be judged in this procedural form. Some new legal provisions result from new model of investigation or from new concept of trial. Some innovations are more consistent and precise. But, there are also illogical and contradictory provisions in code of criminal procedure from 2011.